1998
DOI: 10.1080/1065657x.1998.10701906
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Windrow Composting on Weed Seed Germination and Viability

Abstract: Feedlot manure, containing seeds of twelve weed species, was composted in a windrow to determine whether composting would kill the weed seeds. The twelve species of weeds included: Thfnpsi arvensc, Polygonum comolzwliis, Aiienn fntua, Chenopodium album, Setarin viridis, Galeopsrs tetrahit, Poly,yoiruiri pcrsicorio, Ainnrnnflius retrojlexus, Kochin scopnrin, Gnlium npnrine, Malm rotundrfolm, and Mntrrcnrrn pevfornta. The windrow was managed to maintain core temperatures between 55°C and 65°C for as long as poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 2 publications
3
29
1
1
Order By: Relevance
“…Tompkins et al (1998) found that weed seed viability was zero for wild buckwheat, green foxtail, and stinkweed after 14 d of composting and zero for all 12 weed species in their study after 28 d. In contrast, wild buckwheat was one of the most resilient weeds in our studies. It showed viable seed after 42 d in 1999 (Table 3) and even after 70 d in 1997 (Table 2).…”
Section: Resultscontrasting
confidence: 55%
“…Tompkins et al (1998) found that weed seed viability was zero for wild buckwheat, green foxtail, and stinkweed after 14 d of composting and zero for all 12 weed species in their study after 28 d. In contrast, wild buckwheat was one of the most resilient weeds in our studies. It showed viable seed after 42 d in 1999 (Table 3) and even after 70 d in 1997 (Table 2).…”
Section: Resultscontrasting
confidence: 55%
“…Composting feedlot manure can eliminate kochia seed viability. After 2 wk of composting manure in a windrow, with core temperatures between 55 and 658C, all kochia seed was non-viable (Tompkins et al 1998). In another study, kochia seeds buried in compost were non-viable after 3 d at 508C (Wiese et al 1998).…”
Section: Response To Other Human Manipulationsmentioning
confidence: 99%
“…Seeds of A. retroflexus survived digestion by 10 month-old lambs (Ozer 1982), rumen digestion by cattle (27-45% of the seeds survived) and ensiling followed by rumen digestion (1-6% of the seeds survived) (Blackshaw and Rode 1991). A small percentage of A. retroflexus seeds (3.5%) survived after two weeks of windrow composting at temperatures of 55-65°C (Tompkins et al 1998). Seed dispersal may also occur through the spreading of cow manure, composts or sewage sludge on farmland (Chytil 1986;Eberlein et al 1992;MtPleasant and Schlather 1994).…”
Section: Reproductionmentioning
confidence: 99%
“…Composting manure in a windrow with a core temperature between 55 and 65°C reduced viability of seeds of A. retroflexus to 0% after 4 wk (Tompkins et al 1998). Redroot pigweed seeds preincubated for 1 d in pig slurry and dried for 3 min at 75°C lost viability (Bloemhard et al 1992).…”
Section: Response To Other Human Manipulationsmentioning
confidence: 99%